Problem-based learning for math & science : integrating inquiry and the internet - Ronis, Diane L. 4 0 16; 5 (Thousand Oaks, CA : Corwin Press, 2008)
Explores the effectiveness of problem-based learning and inquiry and how it can be used to strengthen students' understanding of math and science.
Includes bibliographical references (p. 143-148) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching.;Study and teaching.;Study and teaching.;Study and teaching. -- Mathematics;Science;Problem-based learning.;Internet in education.;Mathematics;Science;Problem solving.;Internet in education; 20; 2